Calcium Transport in Specialized Dental Epithelia and Its Modulation by Fluoride - Costiniti, Veronica; Bomfim, Guilherme H.; Mitaishvili, Erna; Son, Ga-Yeon; Li, Yi; Lacruz, Rodrigo S. (Frontiers in Endocrinology, 2021)
Most cells use calcium (Ca2+) as a second messenger to convey signals that affect a multitude of biological processes. The ability of Ca2+ to bind to proteins to alter their charge and conformation is essential to achieve its signaling role. Cytosolic Ca2+ (cCa2+) concentration is maintained low at ~100 nM so that the impact of elevations in cCa2+ is readily sensed and transduced by cells. However, such elevations in cCa2+ must be transient to prevent detrimental effects. Cells have developed a variety of systems to rapidly clear the excess of cCa2+ including Ca2+ pumps, exchangers and sequestering Ca2+ within intracellular organelles. This Ca2+ signaling toolkit is evolutionarily adapted so that each cell, tissue, and organ can fulfill its biological function optimally. One of the most specialized cells in mammals are the enamel forming cells, the ameloblasts, which also handle large quantities of Ca2+. The end goal of ameloblasts is to synthesize, secrete and mineralize a unique proteinaceous matrix without the benefit of remodeling or repair mechanisms. Ca2+ uptake into ameloblasts is mainly regulated by the store operated Ca2+ entry (SOCE) before it is transported across the polarized ameloblasts to reach the insulated enamel space. Here we review the ameloblasts Ca2+ signaling toolkit and address how the common electronegative non-metal fluoride can alter its function, potentially addressing the biology of dental fluorosis.